2018
DOI: 10.1088/1361-648x/aaf08e
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization of an unoccupied molecular orbital with an image potential state at a lead phthalocyanine/graphite interface

Abstract: The interaction of a molecular orbital with a surface state is important to understand the spatial distribution of the wave function at the molecule/substrate interface. In this study, we focus on hybridization of an unoccupied state of lead phthalocyanine (PbPc) with the image potential state (IPS) on a graphite surface. The hybridization modifies the energy-momentum dispersions of the IPS on PbPc films as observed by angle-resolved two-photon photoemission. On the PbPc 1 monolayer film, the IPS band forms a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 49 publications
5
6
1
Order By: Relevance
“…Although an IPS, in general, shows a parabolic band whose effective mass m * is equal to the electron mass m e , two-photon photoemission (2PPE) spectroscopy measurements have revealed that the lowest IPS (LIPS) of PbPc on graphite exhibits a significant increase in the effective mass as m */ m e ≃ 2.2 ± 0.3, , which suggests the influence of the PbPc overlayer. Recently, a similar increase in the effective mass has also been observed for a PbPc overlayer on single crystalline graphite (SCG) …”
Section: Introductionsupporting
confidence: 67%
See 4 more Smart Citations
“…Although an IPS, in general, shows a parabolic band whose effective mass m * is equal to the electron mass m e , two-photon photoemission (2PPE) spectroscopy measurements have revealed that the lowest IPS (LIPS) of PbPc on graphite exhibits a significant increase in the effective mass as m */ m e ≃ 2.2 ± 0.3, , which suggests the influence of the PbPc overlayer. Recently, a similar increase in the effective mass has also been observed for a PbPc overlayer on single crystalline graphite (SCG) …”
Section: Introductionsupporting
confidence: 67%
“…A similar square pattern has long been observed with scanning tunneling microscopy for MPc on highly oriented pyrolytic graphite (HOPG), which can be regarded as a model system of graphene. In particular, Munakata and co-workers have studied intensively the properties of lead phthalocyanine (PbPc) on HOPG ,,, including the image potential states (IPSs), , a set of unoccupied states that exist universally not only on metal but also on insulator and semiconductor surfaces.…”
Section: Introductionsupporting
confidence: 61%
See 3 more Smart Citations